SERTIFIKASI DAN PENINGKATAN KOMPETENSI PROFESIONAL GURU: STUDI NATURALISTIK DI MI NEGERI 2 KOTA PADANG - Amri, Rusmatul; Saputra, Riki; Rahmi, Rahmi (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
Professional competence of teachers is an indicator of the quality of education implementation, because normatively professional teachers will be able to make a quality learning process. However, in reality, the demands for the fulfillment of mandatory tasks for certified teachers are the cause of the lack of efforts to realize quality learning, because the orientation of task implementation as an educator is more focused on fulfilling the number of hours of certified teachers. In accordance with this problem, this study aims to reveal how the professionalism of teachers in the field of Islamic Religious Education at MI Negeri 2 Padang City in carrying out the learning process. In accordance with this goal, this study uses a qualitative nasturalistic approach, namely the research is carried out to reveal the existing reality without any treatment from the researcher. In accordance with the results of the analysis of research data, it can be concluded that the implementation of learning by certified teachers at MI Negeri 2 Padang has no difference with the implementation of learning carried out by teachers who have not been certified. These conclusions are based on data related to tools, planning as well as various aspects related to learning as implemented by certified teachers.